2009
DOI: 10.1111/j.1365-2958.2009.06753.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of the active form of PerR: insights into the metal‐induced activation of PerR and Fur proteins for DNA binding

Abstract: SummaryIn Bacillus subtilis, the transcription factor PerR is an iron dependant sensor of H2O2. The sensing mechanism relies on a selective metal catalysed oxidation of two histidine residues of the regulatory site. Here we present the first crystal structure of the active PerR protein in complex with a Mn 2+ ion. In addition, X-ray absorption spectroscopy experiments were performed to characterize the corresponding iron form of the protein. Both studies reveal a penta-coordinate arrangement of the regulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
154
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(162 citation statements)
references
References 46 publications
7
154
0
1
Order By: Relevance
“…3A). Metal binding to the sensor site promotes a change in PerR conformation from an extended to a more compact form that binds promoter DNA (5,6). The metal-binding-promoted change of PerR to the compact conformation is explained by the fact that H37 and H91, both of which participate directly as metal binding, are located in the two different domains of PerR; thus, these residues can help bring the two PerR domains in each monomer in close proximity and stabilize the compact form.…”
Section: Resultsmentioning
confidence: 99%
“…3A). Metal binding to the sensor site promotes a change in PerR conformation from an extended to a more compact form that binds promoter DNA (5,6). The metal-binding-promoted change of PerR to the compact conformation is explained by the fact that H37 and H91, both of which participate directly as metal binding, are located in the two different domains of PerR; thus, these residues can help bring the two PerR domains in each monomer in close proximity and stabilize the compact form.…”
Section: Resultsmentioning
confidence: 99%
“…Each PerR monomer contains a binding site for a structural Zn 2ϩ as well as a regulatory site that, in B. subtilis, binds either Fe 2ϩ or Mn 2ϩ (46,52) (Fig. 2A).…”
Section: Perrmentioning
confidence: 99%
“…The other resides in the Ddomain, constructed by either four conserved cysteines near the C terminus (C-site) or residues at the surface of the D-domain pointing toward the hinge region (D-site). Structural comparison between inactive apo-and metallated active forms of BsPerR suggested that regulatory metal binding causes DB-domains to swing around the hinge region with respect to the D-domain, from an open (swung-out) to closed (converged) conformations (22)(23)(24). This process leads to a model that the rearrangement of DBdomains by binding a regulatory metal in the hinge region is responsible for the allosteric transition of all Fur family regulators, from the inactive open conformation to the active closed one (23).…”
mentioning
confidence: 99%
“…The mechanisms of metal-specificity and metal-mediated activity modulation have been extensively investigated, revealing some common and specific principles among members of this family. Crystal structures of several metal-bound Fur regulators have been reported for iron-responsive Fur from Pseudomonas aeruginosa (PaFur) (18) and Vibrio cholerae (VcFur) (19), zincresponsive Zur from Mycobacterium tuberculosis (MtZur) (20), nickel-responsive Nur from S. coelicolor (ScNur) (21), and peroxide-sensing PerR from Bacillus subtilis (BsPerR) (22). All of the available structures demonstrate that the Fur family members are homodimeric and each monomer consists of an N-terminal DNAbinding (DB) domain, a C-terminal dimerization (D) domain, and a hinge loop between the two.…”
mentioning
confidence: 99%